Alternatif Solusi Permasalahan Peserta Didik dalam Pelaksanaan Pembelajaran di Sekolah Dasar - Eka Maya Kusuma; Yayuk Setiarini; Agung Setyawan (STIT Fatahillah, 2023)
Educators need a good understanding of psychology before carrying out the educational process so that students get good knowledge as well. Good psychological education from educators will bring good changes for students. The objectives are obtained by understanding the psychology of students 1) Knowing the differences between each student, 2) Knowing the suitable methods used in the teaching and learning process, 3) Knowing the learning styles that are by the differences that exist in students, 4) Making it easier to understand the material will be presented to students. This goal can be achieved by conducting research using qualitative case study methods using interviews and observations with teachers and students. The results showed that there were problems with students in the implementation of learning in elementary schools, such as student laziness in doing assignments that could be overcome by giving punishments and rewards. The conclusion of this study is that there are problems faced by diverse students in the implementation of learning in elementary schools where the alternative solutions provided are different in each problem.